2019
DOI: 10.3390/rs11192200
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Passive Microwave around 183 GHz for Snowfall Detection in the Arctic

Abstract: This study evaluates the potential use of the Microwave Humidity Sounder (MHS) for snowfall detection in the Arctic. Using two years of colocated MHS and CloudSat observations, we develop an algorithm that is able to detect up to 90% of the most intense snowfall events (snow water path ≥400 g m−2 and 50% of the weak snowfall rate events (snow water path ≤50 g m−2. The brightness temperatures at 190.3 GHz and 183.3 ± 3 GHz, the integrated water vapor, and the temperature at 2 m are identified as the most import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Deep neural networks (DNN) are also being adopted as a viable alternative to merge together data from passive and active sensors at high latitudes [182]. This is accompanied by significant progress being made towards using PMW bands around 183 GHz for snowfall detection in Arctic conditions [183]. A better quantification of snowfall at high latitudes [184] and on a global scale [176] Deep neural networks (DNN) are also being adopted as a viable alternative to merge together data from passive and active sensors at high latitudes [182].…”
Section: Observing Snow and Icementioning
confidence: 99%
See 1 more Smart Citation
“…Deep neural networks (DNN) are also being adopted as a viable alternative to merge together data from passive and active sensors at high latitudes [182]. This is accompanied by significant progress being made towards using PMW bands around 183 GHz for snowfall detection in Arctic conditions [183]. A better quantification of snowfall at high latitudes [184] and on a global scale [176] Deep neural networks (DNN) are also being adopted as a viable alternative to merge together data from passive and active sensors at high latitudes [182].…”
Section: Observing Snow and Icementioning
confidence: 99%
“…A better quantification of snowfall at high latitudes [184] and on a global scale [176] Deep neural networks (DNN) are also being adopted as a viable alternative to merge together data from passive and active sensors at high latitudes [182]. This is accompanied by significant progress being made towards using PMW bands around 183 GHz for snowfall detection in Arctic conditions [183]. A better quantification of snowfall at high latitudes [184] and on a global scale [176] will also contribute to unravelling the controversy around the impact of Arctic warming on increased rainfall/snowfall [185] and, more generally, to explaining the differences in model projections between the southern and northern hemispheres and wet and dry regions [186].…”
Section: Observing Snow and Icementioning
confidence: 99%
“…10 and 166 GHz) frequency channels have shown great potentials for retrieving snowfall over snow and ice surfaces (Ebtehaj & Kummerow, 2017). Furthermore, Edel et al (2019) demonstrated that among all MHS channels, near 183 GHz channels are the most important ones to detect snowfall. It should be noted that besides sensitivity towards scattering signatures, high frequency channels are useful to detect snowfall because they are less affected by surface features (Skofronick-Jackson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Their report shows that snowfall rate estimated by combining GMI channels, environmental variables, and infrared bands can be improved over snowfall estimates only from MW channels. A recent study by Edel et al (2019) have demonstrated the ability of MHS channels to detect snow over the Arctic region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation